Revisions of the genera Parhydraena Orchymont, Protozantaena Perkins, Decarthrocerus Orchymont, and Parhydraenopsis nomen novum, aquatic and humicolous beetles from Africa and Madagascar, and comparative morphology of the tribe Parhydraenini (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2009)
The hydraenid genera Parhydraena Orchymont, 1937, Decarthrocerus Orchymont, 1948, Protozantaena Perkins, 1997, and Parhydraenopsis nomen novum are comprehensively revised, based on the study and databasing of 13,323 specimens. Decarthrocerus Orchymont is considered a valid genus, not a subgenus of Parhydraena. A new generic name, Parhydraenopsis nomen novum, is provided to replace Pseudhydraena Orchymont, 1947 (a junior homonym of Pseudhydraena Acloque, 1896). The genera are redescribed, and new species are described in Parhydraena (14), Protozantaena (4), Parhydraenopsis (2), and Decarthrocerus (3). Redescriptions are provided for Parhydraena brevipalpis (Régimbart), P. lancicula Perkins & Balfour-Browne, P. seriata Balfour-Browne, Protozantaena labrata Perkins, Parhydraenopsis cooperi (Orchymont), and Decarthrocerus jeanneli Orchymont. Selected morphological features of Pneuminion Perkins, and members of the tribe Hydraenidini, Hydraenida Germain and Parhydraenida Balfour-Browne, are illustrated and compared with those of members of Parhydraenini. Keys to the genera of Parhydraenini and keys to the species of the genera revised herein are given. Male genitalia, representative spermathecae, antennae, and elytra are illustrated. Scanning electron micrographs of external morphological characters are presented. High resolution digital images of the primary types of all species (except the holotypes of three species, which could not be found) are presented (online version in color), and geographical distributions are mapped. The tribe Parhydraenini has both fully aquatic and humicolous adapted species, and shows notable diversity in the lengths of the maxillary palpi and legs, reflecting the microhabitat type. Humicolous species have relatively short maxillary palpi and tarsi, and often have a specialized body form, as in the very differently shaped members of Discozantaena and Decarthrocerus. Parhydraena has both aquatic and humicolous species, the latter being broad-shouldered species with very short maxillary palpi and tarsi. Protozantaena has one aquatic species, the four other species in the genus being collected by sifting litter in humicolous microhabitats. Species of Decarthrocerus have only been collected by sifting litter; many of the specimens are from bamboo forests. As far as is known, members of Parhydraenopsis are fully aquatic, or found in wet streamside mosses. The following new species are described (type locality in South Africa unless otherwise given): Parhydraena ancylis (Western Cape Province, Heuningnes River), P. asperita (Western Cape Province, Knysna, Diepwalle), P. brahma (Mpumalanga Province, Uitsoek), P. brunovacca (Eastern Cape Province, Umtata, Nquadu Mt.), P. divisa (Sudan, Gilo), P. sebastiani (KwaZulu-Natal Province, Cathedral Peak), P. maculicollis (KwaZulu-Natal Province, Polela River, Himeville), P. maureenae (Western Cape Province, W. Wiedouw farm), P. mpumalanga (Mpumalanga Province, Fanie Botha Trail, Maritzbos Hut area, SW Sabie), P. namaqua (Western Cape Province, Van Rhyns Pass), P. ora (Western Cape Province, Cape Town), P. parva (Western Cape Province, George, Saasveld, Kaaimans River), P. semicostata (Mpumalanga Province, Soutpansberg, Entabeni), P. toro (Western Cape Province, Kirstenbosch, Table Mountain), Protozantaena ankaratra (Madagascar, Antananarivo, Ankaratra, Reserve Manjakatompo, M. Arirana, SE drainage River Ambodimangavo), P. grebennikovi (Tanzania, W. Usambara Mts., Lushoto district, Grant’s Lodge, Mkuzu river, 3–4 km upstream of Kifungilo), P. malagasica (Madagascar, Antsiranana, Parc National Montagne d’Ambre), P. palpalis (Madagascar, Antananarivo, Anjozorobe, Ravoandrina, left affluent of River Ampanakamonty), Parhydraenopsis alta (Ethiopia, Wolamo Province, Mt. Damota), P. simiensis (Ethiopia, Simien Mountains National Park, Jinbar Wenz), Decarthrocerus bambusicus (Democratic Republic of Congo, P. N. Virunga, Volcan Sabinyo, Chanya W., W. Sabinyo), D. mahalicus (Tanzania, Mahali Peninsula, Kungure), D. mbizi (Tanzania, Mt. Mbizi, 12 mi. NE Sumbawanga).